Amalan Doa Mathur Bagi Pencegahan Wabak Covid-19: Kajian Kes di Pondok Pesantren Indonesia: The Practice of Mathur’s Prayer for the Prevention of the Covid-19 Outbreak: Study of Cases in Indonesian Islamic Boarding Schools - Misbah, Muhammad; Malinda Noor Lailatul Qodriyyah (Journal of Quranic Sciences and Research, 2023)
Prevention and handling of Covid-19 for Muslim communities requires endeavor both physically and mentally. The birth initiative is manifested in compliance with the government’s health protocols. Then besides that there is an inner endeavor in the form of prayer. The prayers used are usually based on the al-Qur’an and also the hadith of the Prophet Muhammad. Students at the Islamic Boarding School carry out an inner endeavor through reciting a mature prayer after the maktuba prayer. This study aims to find out the basis for reading mathur prayers, the activities of reading mathur prayers, and the meaning of the activities of reading mathur prayers. The research method is Field research with a qualitative approach. The analysis of this study uses a phenomenological approach with Loewenthal’s theory which divides into 4 aspects, namely: Behavioral Features, Linguistic Features, Cognitive Features, and Emotional Features. The results of the study show that (1) The reading of prayers that are valid at the Al-Ghurobaa’ Kudus Islamic Boarding School began in March 2020 with references to the hadiths of the Prophet Muhammad, narrated by Abu Dawud, who is shahih sanad and matan. (2) The activity of reciting the mathur prayer is carried out after the maktuba prayer led by the imam taking turns praying, starting with reciting the basmalah 10 times, reciting Surah Yasin verse 58 7 times, and finally reciting the mathur prayer. (3) The students’ interpretation of the practice of reciting prayers that are meaningful in Behavoral Features: showing the behavior/adapts of praying; Linguistic Features: shows the language of praise in prayer; Cognitive Features: used as a guide in dealing with epidemics; and Emotional Features: used as a means of getting closer to Allah and His Messenger, growing a sense of security and calm, and having a strong inner self-defense. Pencegahan dan penanganan covid-19 bagi masayarakat muslim membutuhkan ikhtiar baik secara lahir maupun batin. Ikhtiar lahir diwujudkan dalam kepatuhan terhadap protokol kesihatan dari Pemerintah. Kemudian disamping itu ada ikhtiar secara batin berupa doa. Doa yang digunakan biasanya berbasis al-Quran dan juga hadis Nabi Muhammad. Pelajar di Pondok Pesantren melaksanakan ikhtiar batin melalui pembacaan doa yang mathur setelah solat maktubah. Kajian ini bertujuan untuk mengetahui dasar pembacaan doa yang mathur, kegiatan pembacaan doa yang mathur, dan makna dari kegiatan pembacaan doa yang mathur tersebut. Metode penelitian berjenis Field research dengan pendekatan kualitatif. Analisis penelitian ini menggunakan pendekatan fenomenologi dengan teori Loewenthal yang membagi 4 aspek yaitu: Behavioral Features (aspek perilaku), Linguistic Features (aspek bahasa), Cognitive Features (aspek kognitif), dan Emotional Features (aspek emosional). Hasil penelitian menunjukkan bahwa (1) Pembacaan doa yang mathur di Pondok Pesantren Al-Ghurobaa’ Kudus dimulai sejak bulan Mac 2020 dengan rujukan hadis Nabi Muhammad riwayat dari Abu Dawud yang shahih sanad dan matan. (2) Kegiatan pembacaan doa yang mathur dilakukan setelah solat maktubah dengan dipimpin oleh imam sholat secara bergantian, yang diawali dengan membaca basmalah sebanyak 10 kali, membaca Surah Yasin ayat 58 sebanyak 7 kali, dan terakhir pembacaan doa yang mathur. (3) Pemaknaan pelajar tentang praktik pembacaan doa yang mathur secara Behavoral Features: menunjukkan perilaku/adab berdoa; Linguistic Features: menunjukkan bahasa puji-pujian dalam doa; Cognitif Features: dijadikan sebagai pegangan dalam menghadapi wabak; dan Emotional Features: dijadikan sebagai sarana mendekatkan diri kepada Allah dan rasul-Nya, menumbuhkan rasa aman dan tenang, serta mempunyai benteng pertahanan diri secara batin.